Distinguishing alternative reaction pathways by single-molecule fluorescence spectroscopy - Rybina, Arina; Lang, Carolin; Wirtz, Marcel; Grußmayer, Kristin Stefanie; Kurz, Anton; Maier, Frank; Schmitt, Alexander; Trapp, Oliver; Jung, Gregor; Herten, Dirk-Peter (Angewandte Chemie. International edition, 2013)
Focus on chemical transitions: Epoxidation of a double bond in conjugation to a fluorescent dye was studied at single-molecule level. Direct observation of oxirane formation, indicated as a spectral shift from substrate to product state, revealed an alternative reaction pathway for the epoxidation reaction.
Gesehen am 25.01.2022